Consistency Sensitive Operators in CEDR - Goldstein, Jonathan; Hong, Mingsheng; Ali, Mohamed and (2007)
This technical report consists of two concatenated papers. The first is a theoretical paper describing interesting tradeoffs when designing speculative streaming operators. In addition, it describes specific algorithms with specific tradeoffs and the associated complexity analysis for the aggregate operator The second paper describes the other operator algorithms in the overall CEDR context and their associated complexity analyses. In all, the papers describe the necessary operator algorithms for building an efficient, computationally rich, speculative stream processing engine.